Importance of Sustainable Agriculture in Tribal Community of India - Patidar, Jitendra; Kumhar, Bherulal; Mhaske, Suresh; Jat, Seema (International Journal of Bio-resource and Stress Management, 2018)
The sustainable livelihood synthesizes all human activities including five core assets: physical, natural, financial, human and social capital upon which the livelihoods are built.The sustainable livelihood approach aims to find out about livelihoods to improve the design and implementation of poverty reduction efforts. The livelihood assets status of the tribal people in the state of India is the resultant outcome of collective performance of independent variables such as socio-personal (age, education, social participation and family composition), economic (size of land holding, main occupation, housing status, farm power, farm implements, livestock possession, material possession, income from forestry and gross annual income), psychological (level of aspiration, knowledge about forestry practices, adoption of forestry practices and attitude towards forestry), communication (extension contact and use of information sources) and situational (employment status, migration status and utilization of forest resources). The Jharkhand state is bestowed with rich natural resources, abundant biodiversity and excellent human resouvrces.Forest based livelihoods by the tribal people mainly revolve around collection, processing and utilization/selling of various NTFPs like fuel wood, lac, tooth brush, leaves for plate and cup making, fodder and browse, vegetables, fruits, seeds, flowers, bamboos, medicines, mushrooms, oilseeds, oilseed cake, spices, honey, oils, gums, resins, gum-resins, dyes, wax, brooms, fibers, floss, silk, charcoal, fencing, wildlife products, thatches, baskets, ropes, mats, handicrafts, pickles, beverages, abiotic products etc.